Pengaruh Relationship Marketing terhadap Loyalitas Konsumen pada Rafins Indonesia - Triana, Arinda (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to identify the relationship between marketing variables and marketing indicators, namely Trust, Commitment, Communication, and Problem Solving and analyze the impact of this relationship on customer loyalty at Rafins Indonesia. This research is quantitative and uses associative methodology. The population of this study was followers of the Instagram account @rafinsindonesia, totaling 1,342 followers, while the sample consisted of 93 respondents who were Instagram followers of Rafins Indonesia. The sampling technique used is probabilistic sampling, with data sources from primary data and secondary data. Questionnaires and interview methods were used to collect the data required in this investigation, using the Likert scale as the main data collection technique. Research findings show that alpha values are in the range of 0.001 to 0.05, indicating increased customer loyalty through Relationship Marketing strategies. In addition, the estimated t value—8.279, is greater than the t table value of 1.986—resulting in rejection of H0 and acceptance of Ha. This means that the pillars of Relationship Marketing such as commitment, communication, and dispute resolution have a positive and significant influence on customer loyalty at Rafins Indonesia.